Onomatopoeia Dalam Puisi Pilihan Oleh Edgar Allan Poe - Sabrina, Fira (EDUJ : English Education Journal, 2023)
Background of this research is the existence of onomatopoeia in Edgar Allan Poe’s selected poems namely “The Bells” and “The Raven”. The writer uses Ullman’s theory as a reference to analyze the types of onomatopoeia and uses contextual meaning in interpreting the word onomatopoeia in context. The purpose of this study is to find the types of onomatopoeia and also to describe the contextual meaning of onomatopoeia words in selected poems by Edgar Allan Poe. Descriptive Qualitative method used in this research. The analysis begins by identifying words that are onomatopoeic and grouped based on Ullman's theory, namely primary (PO) and secondary (SO) types, then, identifying contextual meanings. This research resulted in 26 words, 15 words in the poem "The Bells" and 11 words in the poem "The Raven". The results of the analysis types of onomatopoeia are 17 words including primary onomatopoeia, and 9 words including secondary onomatopoeia. Analysis of the meaning in the Bells’ Poem, all the words are produced from the sound of objects (Bells). While in The Raven's poem, it is found that there are human, animal (raven) voices and the sounds of other objects.